The impact of the relationship between the updated enterprise risk management framework and the governance system and its reflection on enhancing the company's competitive advantage - Bassim Mohammed Hussein; Ibrahim Hilal Abdulsada Mubarak; Taisir Jawad Kadhim Sultan (Universitas Negeri Malang, 2026)
The research clarifies the consistent variables, including a statement of the impact of the relationship between the updated project risk management framework with its five components: governance and culture, setting objectives and strategy, performance, review, and communication and reporting, with the governance system in determining the organizational structure and responsibilities, improving transparency and reporting, and enhancing the culture of accountability and commitment, and the reflection of the relationship on enhancing the company's competitive advantage. To achieve the research objective, scientific research tools were used, including the design of a scientifically validated questionnaire prepared according to scientific research methods recognized in accounting and statistics. The most prominent conclusions reached by the research were the importance of spreading the culture of risk that accompanies the company's work and urging employees to play a positive role in helping the company transform risks and threats into opportunities that enhance and support the company's competitive advantage, while emphasizing the role of governance boards in establishing a culture of confronting these risks and managing them in recognized ways to achieve the set objectives, generate value, and enhance the company's competitive advantage. Among the most important recommendations was the necessity of having a supervisory and executive board specialized in corporate governance that plans and sets strategies and objectives consistent with these strategies, monitors the implementation process, and identifies the most important risks, gaps, and threats. Accompanying the company's operational work to contribute to enhancing the company's competitive advantage.